PEMBELAJARAN DALAM ERA“NEW NORMAL” DI PONDOK PESANTREN NURUL QARNAIN JEMBER TAHUN 2020 - Hosaini Hosaini (LP2M Universitas Ibrahimy, 2020)
Covid-19 pandemic outbreak not only hits education in kindergarten, elementary level, junior high school, senior high school, and university, but also it hits education in islamic boarding school throughout Indonesia. New Normal is a change in behavior to continue carrying out activities normally but with the addition of implementing health protocols to prevent Covid-19 transmission.This research uses an exploratory case study. The approach uses descriptive qualitative research methods used to obtain information content on the readiness of Pondok Pesantren Nurul Qarnain in carrying out teaching and learning process in the time of Covid-19 pandemic. Teaching and learning activities have been carried out at Pondok Pesantren Nurul Qarnain, by following the health protocol. The advantage of this system is there is no reduction in the learning system. The implementation of teaching and learning activities for students at the pesantrean remains in accordance with curriculum standards. because of the configuration of the board students.